Oxidative Potential of Particles in Different Occupational Environments: A Pilot Study - Sauvain, Jean-Jacques; Deslarzes, Simon; Storti, Ferdinand; Riediker, Michael (The Annals of occupational hygiene, 2015)
The oxidative potential (OP) of particulate matter has been proposed as a toxicologically relevant metric. This concept is already frequently used for hazard characterization of ambient particles but it is still seldom applied in the occupational field. The objective of this study was to assess the OP in two different types of workplaces and to investigate the relationship between the OP and the physicochemical characteristics of the collected particles. At a toll station, at the entrance of a tunnel ('Tunnel' site), and at three different mechanical yards ('Depot' sites), we assessed particle mass (PM4 and PM2.5 and size distribution), number and surface area, organic and elemental carbon, polycyclic aromatic hydrocarbon (PAH), and four quinones as well as iron and copper concentration. The OP was determined directly on filters without extraction by using the dithiothreitol assay (DTT assay-OP(DTT)). The averaged mass concentration of respirable particles (PM4) at the Tunnel site was about twice the one at the Depot sites (173±103 and 90±36 µg m(-3), respectively), whereas the OP(DTT) was practically identical for all the sites (10.6±7.2 pmol DTT min(-1) μg(-1) at the Tunnel site; 10.4±4.6 pmol DTT min(-1) μg(-1) at the Depot sites). The OP(DTT) of PM4 was mostly present on the smallest PM2.5 fraction (OP(DTT) PM2.5: 10.2±8.1 pmol DTT min(-1) μg(-1); OP(DTT) PM4: 10.5±5.8 pmol DTT min(-1) μg(-1) for all sites), suggesting the presence of redox inactive components in the PM2.5-4 fraction. Although the reactivity was similar at the Tunnel and Depot sites irrespective of the metric chosen (OP(DTT) µg(-1) or OP(DTT) m(-3)), the chemicals associated with OP(DTT) were different between the two types of workplaces. The organic carbon, quinones, and/or metal content (Fe, Cu) were strongly associated with the DTT reactivity at the Tunnel site whereas only Fe and PAH were associated (positively and negatively, respectively) with this reactivity at the Depot sites. These results demonstrate the feasibility of measuring of the OP(DTT) in occupational environments and suggest that the particulate OP(DTT) is integrative of different physicochemical properties. This parameter could be a potentially useful exposure proxy for investigating particle exposure-related oxidative stress and its consequences. Further research is needed mostly to demonstrate the association of OP(DTT) with relevant oxidative endpoints in humans exposed to particles.